Spectrum Of Hemoglobinopathies Diagnosed By Hplc In High Prevalence Area Of North Maharashtra - M.VASAIKAR; S. KANTHIKAR; S.CHAVAN (International Journal of Pharma and Bio Sciences, 2012)
The present study aims at evaluating importance of Cation exchange HPLC in high prevalence area in North Maharashtra 4394, samples analyzed in the BIO-RAD variant HPLC system. The retention times, proportion of Hb% and the characteristic of peak for all the Hb fractions were recorded. Screening test and electrophoresis at alkaline PH were done in all cases. Abnormal hemoglobin fractions on HPLC were seen in 2726 cases. HbSA was the predominant in 2253 cases, 270 cases ofHbSS, 183 cases of beta Thalassemia trait, 3 cases of Beta homozygous Thalassemia, 10 cases of Double heterozygous HbS-beta Thalassemia, 3 cases of Hb D trait, 3 cases of Hb E trait and 1 case of Double heterozygous HbE-beta Thalassemia. HPLC was found to be simple, rapid and reliable method. HPLC should be used as an additional method for identification of hemoglobin variant where the work load is more and automation is necessary.